1995
DOI: 10.1128/mcb.15.5.2697
|View full text |Cite
|
Sign up to set email alerts
|

NFATx, a Novel Member of the Nuclear Factor of Activated T Cells Family That Is Expressed Predominantly in the Thymus

Abstract: The nuclear factor of activated T cells (NFAT) regulates cytokine gene expression in T cells through cis-acting elements located in the promoters of cytokine genes. Here, we report the cDNA cloning, chromosomal localization, and initial characterization of a transcription factor related to NFATp and NFATc. The novel molecule, designated NFATx, exhibits in its middle a region very similar to the Rel homology domain in NFATc and NFATp. The amino-terminal region of NFATx also shows significant similarities to cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
193
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(200 citation statements)
references
References 43 publications
6
193
0
1
Order By: Relevance
“…Although this approach does not allow absolute quantification of the amount of mRNA, it is useful for comparing relative expression levels between mRNA species of interest. In the calcineurin A and NFAT families, calcineurin Abe, NFAT4 (13), and NFAT5 (14) were the predominant isoforms expressed in human skeletal muscle. Interestingly, the mRNA expression of NFAT4 and NFAT5 was higher than that of NFAT2, although NFAT2 has been regarded as an important isoform in skeletal muscle development and differentiation (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although this approach does not allow absolute quantification of the amount of mRNA, it is useful for comparing relative expression levels between mRNA species of interest. In the calcineurin A and NFAT families, calcineurin Abe, NFAT4 (13), and NFAT5 (14) were the predominant isoforms expressed in human skeletal muscle. Interestingly, the mRNA expression of NFAT4 and NFAT5 was higher than that of NFAT2, although NFAT2 has been regarded as an important isoform in skeletal muscle development and differentiation (3).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these genes is mediated in part by nuclear factor of activated T-cells (NFAT), a DNA-binding protein that binds to specific sites on the regulatory regions of these genes (reviewed in [1,2]). Molecular cloning studies have demonstrated that at least four different NFAT genes exist, including NFAT p , NFAT c , NFAT3 and NFAT x , all of which contain a Rel homology region that is important for DNA binding [3][4][5][6]. In addition, a serine\proline repeat region of unknown function is present in each of the family members, as well as a putative nuclear localization sequence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a serine\proline repeat region of unknown function is present in each of the family members, as well as a putative nuclear localization sequence. The exact biological function of each of the NFAT proteins is not known, although differences in cell and tissue expression, as well as DNA-binding activity, have been observed [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As for several other transcription factors, NF-AT activity appears to be regulated by subcellular localization and phosphorylation events (Clipstone and Crabtree, 1992) and by interactions between calcineurin and Bcl-2 (Shibasaki et al, 1997). NF-AT is composed of the transcription factor AP-1 and a cytoplasmic subunit, the latter encoded by a family of genes including NFATp, NF-ATc, NF-AT3 and NF-AT4/x Masuda et al, 1995;Northrop et al, 1994). The family members share approximately 70% sequence identity within a region related to the Rel homology domain of the NF-kB transcription factors Northrop et al, 1994).…”
Section: Introductionmentioning
confidence: 99%